Establishment and practice of oncology nurse specialist in the doctor-nurse joint outpatient clinic (肿瘤专科护士在医护联合门诊中工作模式的构建与实践) - SUN Yingning (孙瑛凝); ZHAO Hongwu (赵洪武) (Association of Integrative Nursing, 2022)
This paper summarized the responsibility and role of oncology nurse specialist in the doctor-nurse joint outpatient clinic, and provided reference for the development of specialized nurses in the professional field. Oncology nurse specialist should take the responsibility of providing personalized health assessment, health education, psychological support and follow-up consultation for patients and their families, and they play a role in assisting doctors in diagnosis and treatment. The establishment of model of oncology nurse specialist in the doctor-nurse joint outpatient clinic meets the diversified needs of patients and is feasible and worthy of popularization and application in other disciplines. (本文梳理了肿瘤专科士在医护联合门诊工作模式中的职责与角色功能, 为专科护士在专业领域发展提供依据。肿瘤专科护士在医护联合门诊模式下承担健康评估、宣教指导以及诊疗质量提升等角色功能, 减少了门诊医生诊疗压力, 医护合作相得益彰, 能够满足患者多元化需求, 在医院其他学科的推广也具有可行性。)